Islamophobia & antisemitism in SG : narratives of grievance - Farrow, Luca (2021)
The planned attacks on mosques and a synagogue in Singapore show the international reach of the grievance narratives key to Islamophobia and Antisemitism. Counter-narratives and critical perspectives are required to promote inclusivity in Singapore.